Overcoming current challenges to T-cell receptor therapy via metabolic targeting to increase antitumor efficacy, durability, and tolerability - Mao, Wendy (Frontiers in Immunology, 2022)
The antitumor potential of personalized immunotherapy, including adoptive T-cell therapy, has been shown in both preclinical and clinical studies. Combining cell therapy with targeted metabolic interventions can further enhance therapeutic outcomes in terms of magnitude and durability. The ability of a T cell receptor to recognize peptides derived from tumor neoantigens allows for a robust yet specific response against cancer cells while sparing healthy tissue. However, there exist challenges to adoptive T cell therapy such as a suppressive tumor milieu, the fitness and survival of transferred cells, and tumor escape, all of which can be targeted to further enhance the antitumor potential of T cell receptor-engineered T cell (TCR-T) therapy. Here, we explore current strategies involving metabolic reprogramming of both the tumor microenvironment and the cell product, which can lead to increased T cell proliferation, survival, and anti-tumor cytotoxicity. In addition, we highlight potential metabolic pathways and targets which can be leveraged to improve engraftment of transferred cells and obviate the need for lymphodepletion, while minimizing off-target effects. Metabolic signaling is delicately balanced, and we demonstrate the need for thoughtful and precise interventions that are tailored for the unique characteristics of each tumor. Through improved understanding of the interplay between immunometabolism, tumor resistance, and T cell signaling, we can improve current treatment regimens and open the door to potential synergistic combinations.